Chasing Urartu Alloying Practices: Evaluating Handheld XRF Instruments and Surface Effects for Identifying Zinc-Bearing Copper-Based Alloys - Gueder, Umit; Cavusoglu, Rafet; Ozdemir, Abdulkadir; Ozak, Tolga (Wiley, 2026)
Urartian metalwork is well known for its technological sophistication; however, the classification of copper-based alloys within this corpus, particularly the distinction between standard tin bronzes and zinc-bearing alloys, remains poorly constrained. The identification of such alloys is further complicated by the fundamental limitations of noninvasive analytical techniques. This study systematically evaluates the reliability of handheld x-ray fluorescence (hhXRF) for characterizing Urartian alloys, addressing the diagnostic challenges posed by surface corrosion and instrumental variability. A multi-analytical approach was applied to two distinct belt fragments recovered from the & Ccedil;avu & scedil;tepe Necropolis, identifying one as a standard tin bronze and the other as a ternary (Zn-containing bronze) alloy, to compare surface hhXRF readings against SEM-EDS and metallographic reference data. The investigation was conducted in two phases. First, instrumental reliability was assessed by cross-validating three hhXRF devices against a Certified Reference Material (CRM), establishing an optimized 90-s dual-beam protocol to minimize quantification errors for zinc and tin. Second, the artifacts were subjected to progressive surface cleaning to quantify the masking effects of corrosion. The results demonstrate that surface hhXRF data are strongly affected by corrosion-induced tin enrichment and decuprification, rendering uncleaned and partially cleaned surfaces unreliable for alloy classification. Silicon-rich burial contamination correlates directly with analytical instability, whereas zinc-bearing bronzes exhibit comparatively stable surface signatures. Whereas Zn concentrations remain sensitive to surface stratigraphy, hhXRF provides a qualitatively reliable indicator for the presence of zinc and yields quantitatively accurate results for major alloying elements when supported by appropriate cleaning, extended acquisition times, and repeated measurements. By correlating surface data with depth profiling, this research proposes a diagnostic approach for distinguishing zinc-bearing bronzes from standard bronzes and serves as a preliminary case study for a wider investigation of alloying practices in Urartian metallurgy.
Keywords: copper-based alloys; handheld XRF; Middle Iron Age; Urartu Kingdom; zinc